(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The goal of the present study is to provide a new, straightforward, and verified UV spectrophotometric technique for estimating Olmesartan Medoxomil in commercial formulations like Olmesar 20 and Olmecip 20 (Maclodes Pharmaceutical Ltd.). Materials and Methods: Olmesartan Medoxomil is the member of angiotensin receptor blocker approved by the Food and Drug Administration for the treatment of hypertension. In oral administration, olmesartan medoxomil undergoes intestinal de-esterification to form the active metabolite Olmesartan, which inhibits the binding of angiotensin-I (AT-I) to angiotensin-II (AT-II) receptors in vascular muscle. Results and Discussion: Validation of created analytical techniques in accordance with Intracerebral hemorrhage scale recommendations. In a 10 ml volumetric flask, tablet powder corresponding to 10 mg of olmesartan medoxomil was added. For linearity, accuracy, precision, and robustness, 12 distinct concentrations (ranging from 2 to 24 μg/ml) were formed and the calibration plot was condensed. Statistical analysis shows that these approaches are reliable and specific for estimating olmesartan medoxomil in commercially available tablet formulations. Conclusion: The method outlined for determining olmesartan medoxomil in marketed tablet formulations may be effectively used for routine analysis in quality control laboratories.